Research progress on the role of melatonin and its receptors in animal reproduction: A comprehensive review. (16th April 2018) - Talpur, HS; Chandio, IB; Brohi, RD; Worku, T; Rehman, Z; Bhattarai, D; Ullah, F; JiaJia, L; Yang, L
Contents: Melatonin and its receptors play a crucial role in the regulation of the animal reproductive process, primarily in follicular development. However, the role that melatonin performs in regulating hormones related with reproduction remains unclear. Melatonin and its receptors are present both in female and male animals' organs, such as ovaries, heart, brain and liver. Melatonin regulates ovarian actions and is a key mediator of reproductive actions. Melatonin has numerous effects on animal reproduction, such as protection of gametes and embryos, response to clock genes, immune‐neuroendocrine, reconciliation of seasonal variations in immune function, and silence or blockage of genes. The growth ratio of reproductive illnesses in animals has raised a remarkable concern for the government, animal caretakers and farm managers. In order to resolve this challenging issue, it is very necessary to conduct state‐of‐the‐art research on melatonin and its receptors because melatonin has considerable physiognomies. This review article presents a current contemporary research conducted by numerous researchers from the entire world on the role of melatonin and its receptors in animal reproduction, from the year 1985 to the year 2017. Furthermore, this review shows scientific research challenges related to melatonin receptors and their explanations based on the findings of 172 numerous research articles, and also represents significant proficiencies of melatonin in order to show enthusiastic study direction for animal reproduction researchers.